History Of The Andijan Polkasi (Zien Journal of Social Sciences and Humanities, 2025)
This article provides a comparative analysis of scientific concepts aimed at studying the theoretical foundations and functions of Uzbek dance art. Theoretical ideas about Uzbek dance art are expressed on the basis of a set of scientific and theoretical views on the influence of folk traditional culture on the national dance art, a system of them, and their analysis.